The impact of national cultural distance on deal completion of cross-border M&As targeting firms in Brazil - Köck, Felicitas (2021)
This study contributes to current M&A literature by investigating how differences in national culture influence deal completion of cross-border M&As targeting firms in Brazil, by exploring the effect of differences in four cultural dimensions. A binary logistic regression is estimated based on a sample of 1903 deal attempts between 2007-2017. The results suggest that the influence of national cultural distance is not as detrimental as assumed in the international business literature and that national cultural differences can positively influence deal completion; however, special attention needs to be paid to this issue.